2002
DOI: 10.1097/00126334-200212010-00011
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Developing Peripheral Neuropathy in Patients Coinfected With HIV-1 and HTLV-2

Abstract: One thousand one hundred fifty-two HIV-1-positive patients were screened for HTLV-2 infection, and the AIDS-free coinfected individuals were consecutively included in a longitudinal study with the aim of investigating the role of HTLV-2 in the progression to AIDS and the development of specific neurologic diseases. Two matched HIV-1-positive/HTLV-2-negative controls for each coinfected individual were also enrolled in the study. HTLV-2 infection was found in 95 (8.2%) of the HIV-1-positive patients, 30 of whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 34 publications
2
11
0
3
Order By: Relevance
“…On basis of the clinical findings, some HTLV-II-infected subjects showed peripheral neuropathy during the co-infection and urinary tract infection either in HIV-1/HTLV-II-infected subjects as well in solely infected with HTLV-II. These findings have been shown by other investigators 2,23 , but its pathogenesis remain to be better studied.…”
Section: Discussionsupporting
confidence: 73%
“…On basis of the clinical findings, some HTLV-II-infected subjects showed peripheral neuropathy during the co-infection and urinary tract infection either in HIV-1/HTLV-II-infected subjects as well in solely infected with HTLV-II. These findings have been shown by other investigators 2,23 , but its pathogenesis remain to be better studied.…”
Section: Discussionsupporting
confidence: 73%
“…Although a limited number of studies have shown that HTLV-II-infected individuals are more likely than uninfected individuals to develop neurologic disability, 20 peripheral neuropathy, 21,22 and progressive myelopathy, 23 the role of HIV and/or drugrelated factors could not be excluded. In this study, subjects were seronegative for HIV and only a small percentage reported injection drug use, which we adjusted for in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although less research has focused on HTLV-II, sensory neuropathy has been observed with HTLV-II alone 20 and with HIV coinfection. [20][21][22][23] A spinocerebellar syndrome has also been documented in a few case reports of HTLV-I-and -IIinfected patients. 24 A better understanding of the neurologic abnormalities associated with HTLV infection is important for the clinical care of infected patients.…”
mentioning
confidence: 88%
“…In addition, increased incidence of sensory neuropathy has been reported in IDU infected with HTLV-2 (Dooneief et al, 1996). This association was more pronounced in patients co-infected with HIV-1, whose risk of developing peripheral neuropathy was shown to be three times higher compared with patients infected only with HIV-1 (Zehender et al, 2002). In summary, HTLV-2 has been considered less pathogenic than HTLV-1.…”
Section: Htlv-2: Biological Characteristics Pathogenesis and Epidemimentioning
confidence: 93%